Radar compatible infrared stealth two-dimensional nano composite filler and preparation method thereof
By modifying the transition bimetallic chalcogen compound two-dimensional nanosheets and modifying them using water bath method, the compatibility problem of radar-compatible thermal infrared stealth materials in the existing technology is solved, efficient radar wave absorption and infrared emission compatibility is achieved, and radar stealth performance is significantly improved.
Patent Information
- Application Number
- CN202411914840.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-25
AI Technical Summary
It is difficult to develop radar-compatible thermal infrared stealth materials in the prior art, traditional metal filler radars are incompatible with wave absorption, and semiconductor filler infrared emissivity is high, making it impossible to achieve compatibility between radar wave absorption and infrared emission at the same time.
By using two-dimensional nanosheets of transition bimetallic chalcogen compounds (such as MoWSe2, MoWTe2) and modifying them with positively charged organic macromolecules (such as chitosan, polyethyleneimine), the modification is performed using a water bath method to regulate the impedance and optical characteristics of the nanosheets, and compatibility between radar wave absorption and infrared emission is achieved.
It achieves a low infrared emissivity as low as 0.3 and an effective absorption bandwidth (EBmax) of -10dB reflectance loss up to 3.2GHz, and a reflection loss RLmin can reach -27.0dB@14.2GHz, significantly improving radar stealth performance.
Smart Images

Figure CN119875207A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nanomaterials, and specifically relates to a radar-compatible infrared stealth two-dimensional nanocomposite filler and a preparation method thereof. Specifically, it relates to a radar (2-18GHz) compatible infrared (8-14μm) stealth two-dimensional nanocomposite filler and a preparation method thereof. Background Art
[0002] Since the 1960s, inspired by the camouflage behavior of biological organisms in nature, the United States and the Soviet Union have successively launched research on military target camouflage technology and stealth materials for visible light, radar, thermal infrared and infrared laser bands. Radar and thermal infrared detection account for 60% and 30% of the total detection methods respectively, and research on materials for radar stealth and thermal infrared stealth is also the most extensive. The research on absorbing materials started early, and traditional absorbing media such as carbon-based materials, dielectric ceramics, ferrites, hydroxy iron, magnetic metal powders, and conductive polymers have been maturely applied. New absorbing media such as nano-absorbing materials, chiral materials, and metamaterials have also made great progress in recent years. The research on thermal infrared stealth materials started late, and there are few related reports. In general, traditional thermal infrared stealth materials mainly include stealth coating materials with low infrared emissivity metals or semiconductors as fillers, and new thermal infrared stealth materials mainly include one-dimensional photonic crystals, metamaterials, etc.
[0003] Radar and thermal infrared detection are the two main military detection methods at present. Therefore, the development of radar thermal infrared compatible stealth materials is of great significance to ensure the safety of military targets. In recent years, researchers have achieved low emission in the thermal infrared band (8-14μm) and high absorption characteristics in the radar band (2-18GHz) by designing metasurface-coupled one-dimensional photonic crystal multilayers. However, artificial photonic structures are currently mostly focused on design simulation and theoretical exploration research, which require extremely high processing accuracy, extremely high preparation costs, and immature processing technology, and there is still a large gap from industrial application. In contrast, the processing technology of stealth coating materials is simple and the processing cost is low. Even the most advanced B-2 strategic stealth bomber still uses stealth coating materials. The development of electromagnetic loss compatible thermal low thermal infrared emissivity fillers is the key to achieving radar compatible thermal infrared stealth coating materials. Metal fillers have low infrared emissivity, usually with a thermal infrared emissivity of no more than 0.2, but they have extremely high reflectivity in the visible light and radar bands, resulting in incompatibility of visible light and radar wave stealth. Semiconductor fillers can be modified to achieve electromagnetic loss compatibility with low infrared emissivity characteristics. However, the infrared emissivity of traditional semiconductor fillers represented by metal oxides is still relatively high, and the thermal infrared emissivity value is usually greater than 0.5.
[0004] Two-dimensional materials are a type of layered materials that can be stripped to a thickness of only a few or even a single atomic layer, covering a wide range of materials such as metals, semi-metals, semiconductors, dielectrics, etc. In addition, the stripped two-dimensional nanosheets have a high concentration of exposed atoms on the surface and edges, which can be fully organically modified and the band structure is adjustable. Therefore, by selecting suitable two-dimensional material components and modifying their surfaces, regulating their radar wave absorptivity and infrared emissivity, a series of new radar-compatible thermal infrared stealth two-dimensional nanocomposite fillers can be obtained.
[0005] The prior patent (application number 202210288439.3) discloses a two-dimensional nanosheet composite material modified by organic macromolecules and a preparation method thereof, wherein the composite material is composed of two-dimensional nanosheets and organic macromolecules; the preparation method of the two-dimensional nanosheet composite material modified by organic macromolecules comprises the following steps: S1, blending two-dimensional nanosheets and organic macromolecules in an aqueous liquid phase medium to obtain a mixed dispersion; S2, subjecting the mixed dispersion obtained in step S1 to microwave irradiation to obtain a flocculent precipitate; S3, centrifuging, washing, and vacuum drying the flocculent precipitate obtained in step S2 to obtain two-dimensional nanosheets modified by organic macromolecules. However, the single synthesis amount of the microwave-assisted liquid phase modification method is only in the milligram level, which is not suitable for the large-scale preparation of stealth fillers; and the two-dimensional nanosheet composite material claimed in the prior patent only discloses that it has a low infrared emissivity, that is, it only has infrared stealth performance, and does not claim to have radar wave absorption characteristics, so it cannot be used as a radar wave stealth material. Summary of the invention
[0006] In view of the shortcomings of traditional metal fillers being incompatible with radar absorption and semiconductor fillers having high infrared emissivity, the present invention provides a radar-compatible infrared stealth two-dimensional nano-composite filler and a preparation method thereof. The present invention aims to organically modify two-dimensional nanosheets by a water bath method to obtain a two-dimensional nano-composite material with low infrared emissivity and high radar wave absorption rate, so that the two-dimensional nanosheets have radar-compatible thermal infrared stealth performance.
[0007] The objective of the present invention is achieved through the following technical solutions: <First aspect> A method for preparing a radar-compatible infrared stealth two-dimensional nanocomposite filler comprises the following steps: a. blending the transition bimetallic chalcogenide and the amino-containing organic macromolecule in a buffer to form a mixed dispersion, b The mixed dispersion in step a is heated and rapidly stirred during the heating process to obtain a mixed solution containing flocculent precipitate; c. Centrifuging the mixed solution obtained in step b, collecting the precipitate, washing, and drying to obtain the radar-compatible infrared stealth two-dimensional nanocomposite filler.
[0008] The transition bimetallic chalcogenide comprises MoWSe2 and / or MoWTe2 two-dimensional nanosheets.
[0009] The amino group-containing organic macromolecule is positively charged.
[0010] The amino-containing organic macromolecules include one or more of chitosan and / or polyethyleneimine.
[0011] In step a, the buffer comprises one of tris-hydrochloric acid, disodium hydrogen phosphate-sodium dihydrogen phosphate, disodium hydrogen phosphate-citric acid, and citric acid-sodium citrate buffer; And / or, in step a, the pH value of the buffer solution is in the range of 5-6.5.
[0012] In step a, the concentration of the transition bimetallic chalcogenide in the mixed dispersion is 0.05-0.3 mg / mL.
[0013] In step a, in the mixed dispersion, the concentration ratio of the transition bimetallic chalcogenide compound to the amino-containing organic macromolecule is 1-3:1.
[0014] In step b, the heating is water bath heating; the heating time is 8-24 hours; the heating temperature is 70-100° C.; and the stirring is magnetic stirring (stirring time 8-24 hours, stirring speed 500-2000 rpm).
[0015] In step c, the number of centrifugation treatments is 3-5 times, the centrifugal speed is 1000-3000 rpm, the single centrifugation time is 2-5 minutes, the washing solvent is consistent with the buffer solution in step a, the drying temperature is 40-60° C., and the drying time is 5-24 hours.
[0016] <Second Aspect> The radar-compatible infrared stealth two-dimensional nanocomposite filler prepared by the above-mentioned preparation method also belongs to the protection scope of the present invention.
[0017] In the present invention, the radar wave frequency band is 2-18 GHz, and the infrared wave band is 8-14 μm.
[0018] Compared with the prior art, the present invention has the following beneficial effects: 1) The present invention finds that the two-dimensional nanosheets of transition bimetallic chalcogenides (MoWSe2, MoWTe2) can be modified by positively charged organic macromolecules to form a high-concentration organic-inorganic active interface at the interface of the two-dimensional nanosheets, greatly enhancing the reflectivity of 8-14μm infrared light at the active interface and achieving a low infrared emissivity as low as 0.3; in addition, organic modification can precisely control the impedance of the two-dimensional nanosheets to match the impedance of free space, thereby enhancing the wave absorption characteristics of the two-dimensional nanosheets in the range of 2-18GHz, and the effective absorption bandwidth (EBmax) of -10dB reflection loss can reach 3.2GHz, and the reflection loss RLmin can reach -27.0dB@14.2GHz; this data far exceeds similar materials and has brought a qualitative leap in radar stealth technology.
[0019] 2) The present invention further discovered that in an acidic buffer solution, two-dimensional nanosheets and organic macromolecules containing amino groups (chitosan, polyethyleneimine, etc.) were subjected to water bath modification. On the one hand, the slightly acidic aqueous solvent can make the amino groups on the surface of the organic macromolecule protonated and positively charged, and the surface of the two-dimensional nanosheet negatively charged, with the absolute value of the zeta potential ≥ 20mV, and there is a strong electrostatic adsorption effect between the organic-inorganic components; on the other hand, the amino groups on the surface of the organic macromolecules are not completely protonated in a weakly acidic environment, and there is a hydrogen bond between the amino groups and the sulfide elements of the nanosheets. Therefore, this preparation method can obtain fully organically modified two-dimensional nanosheets with a more stable structure. In addition, the traditional water bath method used in the present invention has a higher yield than the microwave-assisted liquid phase method in the prior art for single modification preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 This is a schematic diagram of the preparation method of the radar-compatible infrared stealth two-dimensional nanocomposite filler of the present invention; Figure 2 This is a reflection loss characteristic diagram of the filler in Example 3 (d=7mm); Figure 3 It is a scatter plot of the minimum reflection loss RLmin of the fillers prepared in Comparative Examples 1-4; Figure 4 This is a graph of the infrared emissivity (8-14 μm) of the fillers of Examples 1-4. DETAILED DESCRIPTION
[0021] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0022] Figure 1 This is a schematic diagram of the preparation method of the radar-compatible infrared stealth two-dimensional nanocomposite filler of the present invention.
[0023] Example 1 0.6 g MoWSe2 two-dimensional nanosheet powder and 0.6 g chitosan powder were mixed in 2000 mL tris-hydrochloric acid buffer (pH=6) to obtain a mixed dispersion; the mixed dispersion was then heated in a water bath at 90°C / 12 h and stirred at high speed with a magnetic stirrer (speed 500 rpm, time 12 h) to generate a flocculent precipitate; the flocculent precipitate was then centrifuged and washed in a 50 mL centrifuge tube with tris-hydrochloric acid buffer (pH=6) at a centrifugal speed of 2500 rpm, a single centrifugation time of 3 min, and a centrifugal washing number of 3 times. The washed precipitate was vacuum dried at 55°C / 8 h to obtain chitosan-modified MoWSe2 two-dimensional nanocomposite filler.
[0024] Example 2 0.2g MoWSe2 two-dimensional nanosheet powder and 0.5g chitosan powder were mixed in 2000mL disodium hydrogen phosphate-sodium dihydrogen phosphate buffer (pH=6) to obtain a mixed dispersion; the mixed dispersion was then heated in a water bath at 75℃ / 14h and stirred at high speed with a magnetic stirrer (speed 1000rpm, time 14h) to generate a flocculent precipitate; the flocculent precipitate was then centrifuged and washed in a 50mL centrifuge tube with disodium hydrogen phosphate-sodium dihydrogen phosphate buffer (pH=6) at a centrifugal speed of 2000rpm, a single centrifugation time of 4min, and a centrifugal washing number of 4 times. The washed precipitate was vacuum dried at 50℃ / 12h to obtain chitosan-modified MoWSe2 two-dimensional nanocomposite filler.
[0025] Example 3 0.5g MoWTe2 two-dimensional nanosheet powder and 1.2g chitosan powder were mixed in 2000mL disodium hydrogen phosphate-citric acid buffer (pH=5.5) to obtain a mixed dispersion; the mixed dispersion was then heated in a water bath at 80℃ / 20h and stirred at high speed with a magnetic stirrer (speed 1500rpm, time 20h) to generate a flocculent precipitate; the flocculent precipitate was then centrifuged and washed in a 50mL centrifuge tube with disodium hydrogen phosphate-citric acid buffer (pH=5.5) at a centrifugal speed of 3000rpm, a single centrifugation time of 5min, and a centrifugal washing number of 5 times. The washed precipitate was vacuum dried at 60℃ / 15h to obtain chitosan-modified MoWTe2 two-dimensional nanocomposite filler.
[0026] Example 4 0.6g MoWTe2 two-dimensional nanosheet powder and 0.6g chitosan powder were mixed in 2000mL citric acid-sodium citrate buffer (pH=5.5) to obtain a mixed dispersion; the mixed dispersion was then heated in a water bath at 95℃ / 22h and stirred at high speed with a magnetic stirrer (speed 2000rpm, time 22h) to generate a flocculent precipitate; the flocculent precipitate was then centrifuged and washed in a 50mL centrifuge tube with citric acid-sodium citrate buffer (pH=5.5) at a centrifugal speed of 1500rpm, a single centrifugation time of 2min, and a centrifugal washing number of 4 times. The washed precipitate was vacuum dried at 45℃ / 10h to obtain chitosan-modified MoWTe2 two-dimensional nanocomposite filler.
[0027] Comparative Example 1 The difference between this comparative example and Example 1 is that MoWSe2 is replaced by an equal amount of MoSe2.
[0028] Comparative Example 2 The difference between this comparative example and Example 3 is that MoWTe2 is replaced by an equal amount of MoTe2.
[0029] Comparative Example 3 The difference between this comparative example and Example 1 is that chitosan is replaced by an equal amount of salmon sperm DNA macromolecules.
[0030] Comparative Example 4 The difference between this comparative example and Example 1 is that the tris-hydrochloric acid buffer solution (pH=6) is replaced by a borax-sodium hydroxide buffer solution (pH=9).
[0031] Application performance test case The materials prepared in Examples 1-4 and Comparative Examples 1-4 were subjected to the following performance tests: 1. Wave absorption characteristics test Test instrument: A vector network analyzer (2-18 GHz, VNA, N5242A PNA-X, Agilent) was used to test and analyze the radar wave absorption characteristics of the prepared two-dimensional nanocomposite filler. The specific test method was the coaxial line method (three-step method).
[0032] Step 1: Ring sample preparation: 30wt.% filler + 70wt.% paraffin, size parameters are as follows: Φout=7.0 mm, Φin=3.04 mm, D=2 mm, oven drying at 40°C; Step 2: Measure the S parameters (S11, S12, S21, and S22), and use the built-in software to calculate the real part ε′ and imaginary part ε″ of the complex permittivity, and the real part μ′ and imaginary part μ″ of the complex magnetic permeability; Step 3: Obtain the reflection loss characteristics, the calculation formula is as follows:
[0033] Where: d, coating thickness, m; c, light speed, 3*10 8 m / s; f, radar wave frequency, Hz; Z0, free space characteristic impedance; Z in , input impedance; u r , ε r are the complex magnetic permeability and complex dielectric constant, respectively.
[0034] Test results: Figure 2 This is the wave absorbing property of the filler in Example 3. Figure 3 It is a scatter plot of the minimum reflection loss RLmin of the fillers of Comparative Examples 1-4.
[0035] From the test results, it can be seen that comparative example 1-2 satisfies -10dB>RLmin>-20dB, and its wave absorption characteristics evaluated by RLmin are inferior to those of embodiment 3; comparative example 3-4 has RLmin>-10dB and has no effective wave absorption characteristics (it is generally believed that the bandwidth of the RL<-10dB part is the effective wave absorption bandwidth).
[0036] 2. Infrared emissivity Test method: Test instrument: The average infrared emissivity of the prepared two-dimensional nanocomposite filler was tested using the IR-2 dual-band infrared emissivity measuring instrument produced by the Shanghai Institute of Technical Physics.
[0037] The test results show that the material prepared by the present invention can achieve a low infrared emissivity as low as 0.3; Figure 4 is the infrared emissivity (8-14 μm) of the fillers of Examples 1-4.
[0038] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a radar-compatible infrared stealth two-dimensional nanocomposite filler, characterized in that: The following steps are involved: a. blending the transition bimetallic chalcogenide and the amino-containing organic macromolecule in a buffer to form a mixed dispersion, b The mixed dispersion in step a is heated and rapidly stirred during the heating process to obtain a mixed solution containing flocculent precipitate; c. Centrifuging the mixed solution obtained in step b, collecting the precipitate, washing, and drying to obtain the radar-compatible infrared stealth two-dimensional nanocomposite filler.
2. The preparation method according to claim 1, characterized in that: In step a, the transition bimetallic chalcogenide comprises MoWSe2 and / or MoWTe2 two-dimensional nanosheets.
3. The preparation method according to claim 1, characterized in that: The amino group-containing organic macromolecule is positively charged.
4. The preparation method according to claim 1, characterized in that: The amino-containing organic macromolecules include one or more of chitosan and / or polyethyleneimine.
5. The preparation method according to claim 1, characterized in that: In step a, the buffer comprises one of tris-hydrochloric acid, disodium hydrogen phosphate-sodium dihydrogen phosphate, disodium hydrogen phosphate-citric acid, and citric acid-sodium citrate buffer; And / or, in step a, the pH value of the buffer solution is in the range of 5-6.
5.
6. The preparation method according to claim 1, characterized in that: In step a, the concentration of the transition bimetallic chalcogenide in the mixed dispersion is 0.05-0.3 mg / mL.
7. The preparation method according to claim 1, characterized in that: In step a, in the mixed dispersion, the concentration ratio of the transition bimetallic chalcogenide compound to the amino-containing organic macromolecule is 1-3:
1.
8. The preparation method according to claim 1, characterized in that: In step b, the heating is water bath heating; the heating time is 8-24 hours; the heating temperature is 70-100° C.; and the stirring is magnetic stirring.
9. The preparation method according to claim 1, characterized in that: In step c, the number of centrifugal treatments is 3-5 times, the centrifugal speed is 1000-3000 rpm, the single centrifugal time is 2-5 minutes, the drying temperature is 40-60° C., and the drying time is 5-24 hours.
10. A radar-compatible infrared stealth two-dimensional nanocomposite filler prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Organic macromolecule-modified two-dimensional nanosheet composites and their preparation methods
CN114773690B